1991
DOI: 10.1159/000186413
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Vascular Access for Acute Renal Failure: Using Buselmeier Shunt and Femoral Vessel Catheter

Abstract: Three types of vascular access were evaluated over a period of 2 years, January 1987-December 1989, in 76 critically ill acute renal failure (ARF) patients. The Buselmeier shunt comprised 75% of the acute vascular access which were utilized, the cannulation of the femoral vessel 23% and the Scribner shunt 2%. The Buselmeier shunt was successfully used alone (mainly in the forearm) in 58 patients for continuous arteriovenous hemofiltration, continuous arteriovenous hemodialysis and intermittent hemofiltration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Their main limitation is the relatively low blood flows, especially when inadequate vessels allow only the entry of small gauge vessel tips. Alarabi et al have reported on the successful use of Buselmeier shunts (24). These have arterial and venous side-arms arising from the main shunt loop.…”
Section: Arteriovenous Accessmentioning
confidence: 99%
“…Their main limitation is the relatively low blood flows, especially when inadequate vessels allow only the entry of small gauge vessel tips. Alarabi et al have reported on the successful use of Buselmeier shunts (24). These have arterial and venous side-arms arising from the main shunt loop.…”
Section: Arteriovenous Accessmentioning
confidence: 99%
“…Usually, a Buselmeier shunt was preferred because, from our experience, it is reliable, gives adequate blood flow and is easy to bypass if there is clotting [5]. An alternative method o f cannulation of the femoral vessels by femoral catheters is the Mahurkar (Quinton Instrument, Seattle.…”
Section: Vascular Access and Anticoagulationmentioning
confidence: 99%